Marine protected areas in the management of artisanal fisheries - Sultan, Mohammed Akthar Riad (School of Economics, 2019)
This thesis examines spatial patterns of effort by fishers in waters adjoining a marine protected area, and their impacts on the reserve’s ability to reduce the impacts of overfishing. The artisanal fisheries operating near Blue Bay Marine Park, Mauritius, provided case-study data for analysis. Two forms of spatial connectivity were evaluated. The first focused on spillovers of adult and juvenile fish from the MPA. Data on catch and geographical fishing location were collected from a sample of fishers over 12 months. Assessment of spillover gradients using Generalised Linear Models and economic production functions found evidence of spillovers up to 4 km from the MPA. The second connectivity study modelled fishers’ spatial behaviour, using a random utility framework and random parameters logit estimation. Fishers appeared sensitive to the expected catch, its variability, human risk and distance travelled. Expected catch and catch variability were modelled using a Just and Pope production function. The two connectivities were integrated in bioeconomic models to assess the relationship between reserve size, fishing effort and harvests. Using a Beverton and Holt recruitment function, an age-structured bioeconomic model for the dominant target species, Unicorn fish (Naso unicornis), was constructed from the catch data. In the hypothetical case of an initially over-exploited fishery, an inverted-U relationship between fisheries benefits and the Marine Park’s size was observed. No pre-reserve data was available for use as a counterfactual; the model was therefore used to estimate the pre-reserve population. This was then used to assess the performance of the Marine Park in enhancing fish population and biomass. In the light of the findings, the thesis concludes that the extent and magnitude of fishing effort should be considered when debating the placement and size of marine reserve, and proposes a step-wise approach to integrate fishers’ behaviour in the evaluation of existing and new MPAs.